A Comparative Study of Mental Alertness Between Inactive and Active Individuals In Baghdad University Students Aged 18 – 22 Years Old - Ismael, Hiwada; Hikmat, Tiba (Journal of Physical Education, 2016)
The importance of the study lies in using modern up dated techniques in teaching like mental alertness and its effect on the field of sport. The problem of the study was the lack of attention in university of Baghdad students as well as their inability to multi task. Most students seem distracted and rarely use previous experiences to solve new problems. The research aimed at identifying the level of mental alertness in active and inactive individuals in both humanities and scientific colleges in the University of Bagdad as well as comparing between active and inactive individuals according to gender and age as well as specialization. The researcher used the descriptive method. The subjects were (1200) college student both male and female. The researcher used mental alertness scale that consisted of 36 items divided on four fields. A pilot study was conducted on 20 students following by the main inventory. The data was collected and treated using proper statistical operations. The researchers concluded that all female students got the same level of mental alertness (good). In addition to that they concluded there are no differences in mental alertness in female college students in variables of age and gender which shows that mental alertness depends entirely on mental abilities. They finally recommended making studies on mental alertness and its relationship with psychological variables like physiological stability and so on, also making studies on levels of mental alertness on other samples.